Is overweight associated with periodontitis in pregnant women? Systematic review and meta-analysis - Gerson Aparecido Foratori-Junior; Priscilla Ramos Pereira; Isabella Antunes Gasparoto; Silvia Helena de Carvalho Sales-Peres; Juliana Moura Storniolo de Souza; Shahrukh Khan (Japanese Dental Science Review, 2022)
This systematic review and meta-analysis aimed to generate pooled evidence for the association between excessive weight and pregnancy induced periodontitis. EMBASE, SCOPUS, PubMed/MEDLINE, Web of Science, BVS/LILACS, Cochrane Library and SCIELO databases were accessed. Eligibility criteria were: human clinical studies published between year 2000 and 2021. Newcastle-Ottawa scale was used to evaluate risk of bias of the studies. Meta-analysis was performed using MedCalc® Statistical Software. Eleven studies were included, evaluating 2152 pregnant women (743 with overweight/obesity and 1409 with normal body mass index - BMI), with a mean age of 29.62 years. Most studies had low risk of bias. A positive association between overweight/obesity and periodontitis was found, with an average of 61.04% of women with overweight/obesity and periodontitis, showing the overall random-effects relative risk and 95% CI of 2.21 (1.53–3.17) (p < 0.001). Arterial hypertension, gestational diabetes mellitus and excessive gestational weight gain were the most common adverse effects of maternal obesity that may have been linked to periodontitis induced pro-inflammatory state. In conclusion, a positive association was found between overweight/obesity and periodontitis during pregnancy. However, the high heterogeneity between the studies related to sample size, periodontal classification and the cutoff-points for BMI are the main limitation.